2022
DOI: 10.1039/d2gc02906e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre-treatment of herbaceous feedstocks on behavior of inorganic constituents under chemical looping gasification (CLG) conditions

Abstract: Biomass Chemical looping gasification (BCLG) is a promising key technology for producing carbon neutral liquid biofuels. However, various ash-related issues, such as bed agglomeration, fouling and slagging or high-temperature corrosion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…b Elemental mapping of the surface of a parti-cle in the bottom ash (BA) from day 13 and c mapping of a particle, exposing its porous interior, obtained from different parts of the process on day 13, reprinted with permission of Elsevier from (Stanicic et al 2021) as observed by scanning electron microscopy and energy dispersive X-ray spectroscopy analysis (Ge et al 2022). In order to minimise the impact of biomass ash on the process, pretreatment was applied to biomasses such as torrefaction, leaching, and combination, which significantly improve the ash related characteristics (Lebendig and Müller 2022). Chlorine content was decreased by the application of torrefaction, but not the content of potassium.…”
Section: Ash and Alkali-alkaline Earth Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…b Elemental mapping of the surface of a parti-cle in the bottom ash (BA) from day 13 and c mapping of a particle, exposing its porous interior, obtained from different parts of the process on day 13, reprinted with permission of Elsevier from (Stanicic et al 2021) as observed by scanning electron microscopy and energy dispersive X-ray spectroscopy analysis (Ge et al 2022). In order to minimise the impact of biomass ash on the process, pretreatment was applied to biomasses such as torrefaction, leaching, and combination, which significantly improve the ash related characteristics (Lebendig and Müller 2022). Chlorine content was decreased by the application of torrefaction, but not the content of potassium.…”
Section: Ash and Alkali-alkaline Earth Metalsmentioning
confidence: 99%
“…Chlorine content was decreased by the application of torrefaction, but not the content of potassium. By changing the molar ratio of Si/(Ca + Mg) may affect the ash fusion; the higher the ratio, the higher the ash fusion temperature (Lebendig and Müller 2022).…”
Section: Ash and Alkali-alkaline Earth Metalsmentioning
confidence: 99%